Potential Sources and Roles of Adaptive Immunity in Age-Related Macular Degeneration: Shall We Rename AMD into Autoimmune Macular Disease? - Camelo, Serge (Hindawi Publishing Corporation, 2014)
Age-related macular degeneration (AMD) is the leading cause of vision loss in the elderly throughout the industrialized world. Its most prominent pathologic features are lesions involving the retinal pigment epithelium (RPE) the Bruch's membrane, the degeneration of photoreceptors, and, in the most aggressive cases, choroidal neovascularization. Genetic associations between the risk of developing AMD and polymorphism within components of the complement system, as well as chemokine receptors expressed on microglial cells and macrophages, have linked retinal degeneration and choroidal neovascularization to innate immunity (inflammation). In addition to inflammation, players of the adaptive immunity including cytokines, chemokines, antibodies, and T cells have been detected in animal models of AMD and in patients suffering from this pathology. These observations suggest that adaptive immunity might play a role in different processes associated with AMD such as RPE atrophy, neovascularization, and retinal degeneration. To this date however, the exact roles (if any) of autoantibodies and T cells in AMD remain unknown. In this review we discuss the potential effects of adaptive immune responses in AMD pathogenesis.